Fanconi anemia pathway regulation by FANCI in prostate cancer - Kaljunen, Heidi; Taavitsainen, Sinja; Kaarijärvi, Roosa; Takala, Eerika; Paakinaho, Ville; Nykter, Matti; Bova, G. Steven; Ketola, Kirsi (Frontiers in Oncology, 2023)
Prostate cancer is one of the leading causes of death among men worldwide and thus research on the genetic factors enabling the formation of treatment resistant cancer cells is crucial for improving patient outcomes.Here, we report a cell-line specific dependence on FANCI and related signalling pathways to counteract effects of DNA damaging chemotherapy in prostate cancer. Our results reveal that FANCI depletion results in significant downregulation of Fanconi anemia (FA) pathway members in prostate cancer cells indicating that FANCI is an important regulator of FA pathway. Furthermore, we found that FANCI silencing reduces proliferation in p53-expressing prostate cancer cells. This extends the evidence that inactivation of FANCI may convert cancer cells from a resistant to an eradicable state under the stress of DNA-damaging chemotherapy. Our results also indicate that high expression of FA pathway genes correlates with poorer survival in prostate cancer patients. Moreover, genomic alterations of FA pathway members are prevalent in prostate adenocarcinoma patients; mutation and copy number information for the FA pathway genes in seven patient cohorts (N = 1732 total tumor samples) reveals that 1025 (59.2%) tumor samples have an alteration in at least one of the FA pathway genes, suggesting that genomic alteration of the pathway is a prominent feature in patients with the disease.